The Urgency Of Mediator’s Good Faith In Mediating Legal Disputes: The Critical Analysis Study - Jasmaniar Jasmaniar; Zainuddin Zainuddin (Fakultas Hukum Universitas Mataram, 2022)
This study aims to explore the concept and urgency of mediator’s good faith in mediating civil law. It is a normative juridical study (doctrinal) with secondary data from primary and secondary legal materials, using bibliography technique. Those materials are analyzed with a qualitative descriptive method. Further, good faith is put as the highest principle in agreement, including mediation and expecting to be implemented by all dispute parties and mediators as well. A mediator’s good faith should be carried out with earnest effort and intention formerly, instead of pushed by constitution to mandatory mediating dispute parties. This study has shown that good faith visibly implements if the mediator actively conducts the functions and responsibilities with confidentiality, volunteer, empowerment, neutrality, and exclusive solutions as the principles.